A Summary of Chinese Expert Consensus on Fetal Growth Restriction (An Update on the 2019 Version). Issue 3 (22nd July 2022) - ,; Sun, Luming; Hu, Yali; Qi, Hongbo
Abstract : Abstract: Fetal growth restriction (FGR) is a common complication of pregnancy associated with higher rates of perinatal mortality and morbidity, as well as a variety of long-term adverse outcomes. To standardize the clinical practice for the management of FGR in China, Fetal Medicine Subgroup, Chinese Society of Perinatal Medicine, Chinese Medical Association and Maternal-Fetal Medicine Committee, Chinese Society of Obstetrics and Gynecology, Chinese Medical Association organized an expert committee to provide official consensus-based recommendations on FGR. We evaluated the evidence provided by relevant high-quality literature, performed a three-round Delphi study and organized face-to-face meetings with experts from multidisciplinary backgrounds. The consensus includes the definition, prenatal screening, prevention, diagnosis, monitoring and management of FGR.